Safety and utility of acute electroconvulsive therapy for agitation and aggression in dementia. (16th May 2014) - Acharya, Deepa; Harper, David G.; Achtyes, Eric D.; Seiner, Stephen J.; Mahdasian, Jack A.; Nykamp, Louis J.; Adkison, Lesley; Van der Schuur White, Lori; McClintock, Shawn M.; Ujkaj, Manjola; Davidoff, Donald A.; Forester, Brent P.
<x xml:space="preserve">Abstract</x> Objective Agitation and aggression are among the most frequent and disruptive behavioral complications of dementia that contribute to increased cost of care, hospitalization, caregiver burden, and risk of premature institutionalization. This current study examined the safety and efficacy of electroconvulsive therapy (ECT) as a treatment for behavioral disturbances in dementia. We hypothesized that ECT would result in reduced agitated and aggressive behaviors between baseline and discharge. Methods Twenty‐three participants admitted to McLean Hospital (Belmont, MA, USA) and Pine Rest Christian Mental Health Services (Grand Rapids, MI, USA), with a diagnosis of dementia who were referred for ECT to treat agitation and/or aggression, were enrolled in the study. We administered the Cohen‐Mansfield Agitation Inventory–Short Form, Neuropsychiatric Inventory–Nursing Home Version, Cornell Scale for Depression in Dementia, and the Clinical Global Impression Scale at baseline, during, and after the ECT course. Results Regression analyses revealed a significant decrease from baseline to discharge on the Cohen‐Mansfield Agitation Inventory (F(4, 8) = 13.3; p = 0.006) and Neuropsychiatric Inventory (F(4, 31) = 14.6; p < 0.001). There was no statistically significant change in scores on the Cornell Scale for Depression in Dementia. The Clinical Global Impression scores on average changed from a rating of "markedly agitated/aggressive" at baseline to "borderline agitated/aggressive" at discharge. Treatment with ECT was well tolerated by most participants; discontinuation of ECT occurred for two participants because of recurrence of agitation and for three participants because of adverse events. Conclusions Electroconvulsive therapy may be a safe treatment option to reduce symptoms of agitation and aggression in patients with dementia whose behaviors are refractory to medication management. Copyright © 2014 John Wiley & Sons, Ltd.